Dyslipidaemia prevalence and associated risk factors in the United Arab Emirates: a population-based study. Issue 11 (7th November 2019) - Mahmoud, Ibrahim; Sulaiman, Nabil
Abstract : Objectives: To determine and describe the prevalence and pattern of dyslipidaemia and its associated risk factors among an adult Emirati population. Design: Population-based, cross-sectional study. Setting: Adults living in the Northern Emirates. Participants: 824 adult participants (51.8% men, 48.2% women, mean age 42.8±13.4 years old). Primary outcome measures: Fasting blood samples were collected, blood pressure and waist circumference were measured. Results: The overall dyslipidaemia prevalence was 72.5%, with 42.8% of the participants showing high total cholesterol (TC) level, 29% showing high triglyceride (TG) level, 42.5% showing low high-density lipoprotein cholesterol (HDL-C) level, 38.6% showing high low-density lipoprotein cholesterol (LDL-C) level and 72.3% showing high cholesterol ratio. The regression models showed that gender was a significant predictor of a high TG level, low LDL-C level and high cholesterol ratio. Middle-aged individuals (30–59 years old) had a significantly higher risk of having high TC, TG and LDL-C levels than young (<30 years old) and elderly (≥60 years old) individuals. Diabetes mellitus was a significant predictor of low TC, high TG and low HDL-C levels, while central obesity was a significant predictor of a high TG level, low HDL-C level and high cholesterol ratio. Smoking was a significant predictor of a high TG level only in men. Conclusions: The prevalence of dyslipidaemia was considerably high among the local adult Emiratis. The identified dyslipidaemia predictors were gender, age, smoking, central obesity and diabetes. Further studies are recommended to assess other important risk factors and aggressive preventive measures in the United Arab Emirates.